How professional and academic pre-qualifications relate to success in medical education: results of a multicentre study in Germany - Schröpel, Carla; Festl-Wietek, Teresa; Herrmann-Werner, Anne; Wittenberg, Tim; Schüttpelz-Brauns, Katrin; Heinzmann, Andrea; Keis, Oliver; Listunova, Lena; Kunz, Kevin; Böckers, Tobias M.; Herpertz, Sabine; Zipfel, Stephan; et al. (PLOS ONE, 2024)
Objective Every year, many applicants want to study medicine. Appropriate selection procedures are needed to identify suitable candidates for the demanding curriculum. Although research on medical school admissions has shown good predictive validity for cognitive selection methods (undergraduate GPA, aptitude tests), the literature on applicants with professional and/or academic experience prior to entering medical school remains slim. In our study, we therefore aimed to examine the association between academic success in medical school and having previously completed vocational training in the medical field, voluntary service (≥11 months) or an academic degree. Methods Data were collected in a multicentre, cross-sectional study at five medical schools in Germany (Baden-Wuerttemberg) from students during medical school (i.e. 3rd-, 6th-, and 10th-semester and final-year students). Academic success was assessed according to scores on the first and second state examinations, the total number of examinations repeated and the number of semesters beyond the standard period of study. For the analysis we calculated ordinal logistic regression models for each outcome variable of academic success. Results A total of N = 2,370 participants (response rate: RR = 47%) participated in the study. Having completed vocational training was associated with a higher amount of repeated examinations (small effect), while having an academic degree was associated with worse scores on the second state examination (medium effect). No significant association emerged between voluntary service and academic success. Conclusion The results indicate that professional and academic pre-qualifications pose no advantage for academic success. Possible associations with the financing of study and living conditions of students with pre-qualifications were analysed and discussed in an exploratory manner. However, the operationalisation of academic success from objective and cognitive data should be critically discussed, as the benefits of prior experience may be captured by personal qualities rather than examination results.